Modification of the Mercosur Social-Labor Declaration (2015): an advance in the construction of the social dimension of the integration process - Castello, Alejandro (2016)
This contribution analyzes the role fulfilled by International Labor Standards and, specifically, by social clauses in Free Trade Conventions and Agreements, as a way of preventing social dumping and building a social dimension in the globalization and regionalization of economy. The author offers the case of the MERCOSUR Labor and Social Declaration, issued in 2015, which amends that of the year 1998, studying its contents, legal efficacy and supervision mechanisms. He emphasizes the fact that social charters generally limit themselves to recognizing fundamental or basic labor rights already found in the legislation of the member countries, but which are nonetheless useful for hindering attempts to deregulate or relax social and labor provisions.